Prophet Shu’ayb (peace be upon him) and his multiple messages: An analytical study of the differing descriptions and the destruction of his people in light of the Qur’an: https://doi.org/10.5281/zenodo.17101956 - Abdul Majeed; Awais Khan; Sadheer Khan (Mufti Muhammad Hassan); Awais Ud din Khan (Journal of Religion and Society, 2025)
This study explores the differing descriptions of the people associated with Prophet Shuʿayb (peace be upon him) in the Qur'an, where they are referred to as the people of Madyan in some verses and the companions of al-Ayka in others. The research investigates whether these designations refer to two distinct nations or one, through a comparative analysis of Qur'anic narratives and classical tafsīr (exegesis). The findings align with the majority scholarly view that the variation in terminology reflects contextual emphasis rather than indicating separate communities, thereby underscoring the Qur’an’s rhetorical and thematic richness. The study also addresses the apparent differences in the punishment narratives, showing how they contribute to a unified thematic message. Key words: Prophet Shoaib, People of Madyan and Companion of Alayka, Punishment Narratives of Prophet Shuaib’s People, Contextual Interpretation in the Quran, Multiple Prophetic Missions in the Quran, Quranic Narrative Rhetoric